Performance and egg quality of laying hens fed flaxseed: highlights on n-3 fatty acids, cholesterol, lignans and isoflavones. (7th November 2016) - Mattioli, S.; Ruggeri, S.; Sebastiani, B.; Brecchia, G.; Dal Bosco, A.; Cartoni Mancinelli, A.; Castellini, C.
Abstract : Flaxseed is a rich source of α -linolenic acid and phytoestrogens, mainly lignans, whose metabolites (enterodiol and enterolactone) can affect estrogen functions. The present study evaluated the influence of dietary flaxseed supplementation on reproductive performance and egg characteristics (fatty acids, cholesterol, lignans and isoflavones) of 40 Hy-Line hens (20/group) fed for 23 weeks a control diet or the same diet supplemented with 10% of extruded flaxseed. The flaxseed diet had approximately three times the content of lignans (2608.54 ng/g) as the control diet, mainly secoisolariciresinol diglucoside (1534.24 v . 494.72 ng/g). When compared with the control group, hens fed flaxseed showed a similar deposition rate (72.0% v . 73.9%) and egg yield. Furthermore, there was no effect of flaxseed on the main chemical composition of the egg and on its cholesterol content. Estradiol was higher in the plasma of the control group (1419.00 v . 1077.01 pg/ml) probably due to the effect of flaxseed on phytoestrogen metabolites. The plasma lignans were higher in hens fed flaxseed, whereas isoflavones were lower, mainly due to the lower equol value (50.52 v . 71.01 ng/ml). A similar trend was shown in eggs: the flaxseed group had higher level of enterodiol and enterolactone, whereas the equol was lower (198.31 v . 142.02 ng/g yolk). Secoisolariciresinol was the main lignan in eggs of the flaxseed group and its concentration was three times higher then control eggs. Flaxseed also improved the n-3 long-chain polyunsaturated fatty acids of eggs (3.25 v . 0.92 mg/g egg), mainly DHA, however, its oxidative status (thiobarbituric reactive substances) was negatively affected. In conclusion, 10% dietary flaxseed did not affect the productive performance of hens or the yolk cholesterol concentration, whereas the lignans and n-3 polyunsaturated fatty acid content of eggs improved. Further details on the competition between the different dietary phytoestrogens and their metabolites (estrogen, equol, enterodiol and enterolactone) should be investigated.